2004
DOI: 10.1109/tap.2004.832371
|View full text |Cite
|
Sign up to set email alerts
|

Ground Influence on the Input Impedance of Transient Dipole and Bow-Tie Antennas

Abstract: Abstract-In this paper, the influence of a lossy ground on the input impedance of dipole and bow-tie antennas excited by a short pulse is investigated. It is shown that the ground influence on the input impedance of transient dipole and bow-tie antennas is significant only for elevations smaller than 1 5 of the wavelength that corresponds to the central frequency of the exciting pulse. Furthermore, a principal difference between the input impedance due to traveling-wave and standing-wave current distributions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 15 publications
1
22
0
Order By: Relevance
“…It can be seen that the presence of the marble does not significantly influence the input-impedance values when the antenna is located at elevations higher than of the wavelength corresponding to the central frequency of the excitation signal (12 cm). This corroborates the results presented in [9] and [25], where similar behavior was reported for a PEC thin-wire bow-tie antenna. We, also, find than the coupling between the antenna and the ground increases the fidelity of the antenna response, as the lossy ground acts as an extra resistive load on the wire.…”
Section: Numerical Resultssupporting
confidence: 92%
“…It can be seen that the presence of the marble does not significantly influence the input-impedance values when the antenna is located at elevations higher than of the wavelength corresponding to the central frequency of the excitation signal (12 cm). This corroborates the results presented in [9] and [25], where similar behavior was reported for a PEC thin-wire bow-tie antenna. We, also, find than the coupling between the antenna and the ground increases the fidelity of the antenna response, as the lossy ground acts as an extra resistive load on the wire.…”
Section: Numerical Resultssupporting
confidence: 92%
“…The boundaries of the FDTD volume are terminated using the uniaxial perfectly matched layer (UPML) absorbing boundary conditions. The UPML is composed of a number of cells with a specific profile of the electric and magnetic properties and is backed by perfectly conducting walls [8].…”
Section: Electromagnetic Modeling Of the Gpr System Using Fdtdmentioning
confidence: 99%
“…In [2], a separated-aperture sensor which consists of two dipoles housed in corner reflectors that are separated by a metallic septum is discussed and simulated using the FDTD method. In [3,4,10,12], an efficient bowtie antenna for GPR system is developed to exhibit good efficiency in ultra-wide band using a combination of a tapered capacitive and resistive loading.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the problem pertains to an antenna matching problem. We have learned that when an antenna is situated in a proximity to the ground its input impedance varies significantly with the antenna elevation and the type of the ground [1], [2]. From the system point of view, such input impedance variation is disadvantageous as it leads to difficulty in maintaining a matched condition at the antenna's terminal.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that the input impedance of typical GPR antennas (i.e., dipoles and bow ties) fluctuates more with antenna elevation for a larger dielectric permittivity of the ground [2]. Moreover, it has been found that the fluctuation is significant only for very small distances (i.e., a fraction of the wavelength corresponding to the central frequency of the exciting pulse) from the ground [2].…”
Section: Introductionmentioning
confidence: 99%